Mechanical properties of novel hybrid bamboo fibre/ aluminium mesh reinforced polymer composite - Ismail, Nik Ainun Nik; Halip, Juliana Abdul; Roslan, Mohd Nazrul; Ismail, Al Emran; Baharuddin, Norhazaedawati; Kamarudin, Khairu; Shaari, Muhammad Farid (Universiti Putra Malaysia Press, 2024)
Bamboo fibres are one of the sustainable lignocellulosic resources explored for polymer composites in recent years. Research has shown that bamboo fibres have the potential to be used in a variety of critical applications. Nevertheless, bamboo fibres are susceptible to thermal and hygroscopic loads, and their mechanical properties are limited by the unequal interfacial strength and varying fibre dimensions. Implementing hybrid procedures or incorporating alternative materials, such as aluminium metal, is strongly advised to address this issue. Thus, this study investigates the tensile and flexural performances of the hybrid bamboo fibre/aluminium expanded mesh-reinforced polymer composites. The composites were fabricated using epoxy resin reinforced with bamboo fibre, and an aluminium expanded mesh sheet was constructed using a vacuum infusion process utilising various stacking sequences and mesh sizes. The test findings indicated that the composite material exhibited tensile stress values ranging from 27 to 34 MPa and a corresponding tensile strain value between 1.1% and 1.6%. The flexural strength and strain values were measured within the range of 44 Mpa to 59 Mpa and 2.2% to 3.2%, respectively. ANOVA analysis showed that both stacking sequences and mesh size significantly affected the tensile performances of the composites, while only stacking sequences affected the flexural performance significantly. Overall, a hybrid composite of bamboo fibre and aluminium mesh is well-suited as a substitute material in industries requiring exceptional mechanical properties.